Model Reference Control of Hyperchaotic Systems - Pengfei Zhao; Cai Liu; Xuan Feng (Journal of Applied Mathematics)
We have applied a famous engineering method, called model reference control, to control hyperchaos. We have proposed a general description of the hyperchaotic system and its reference system. By using the Lyapunov stability theorem, we have obtained the expression of the controller. Four examples for the both certain case and the uncertain case show that our method is very effective for controlling hyperchaotic systems with both certain parameters and uncertain parameters.